Transformation and Regeneration Protocol for Two Farmer Preferred Open Pollinated Tropical Maize (Zea Mays) Varieties - Neondo, J.O.; Alakonya, A.E.; Matheka, J.; Masanga, J.O.; Kasili, R.W. (Science Publishing Group, 2016)
Abstract: In vitro regeneration of open pollinated varieties (OPVs) Kakamega Striga Tolerant Population 94 (KSTP’94) and ‘Namba Nane’ alongside a tropical inbred line (CML144) was evaluated using immature zygotic embryos as explants. Four callus induction media (CIM) regimes; Murashige and Skoog (MS), Linsmaier and Skoog (LS), Chu (N6) and N6*(N6 medium fortified with 0.35 gL-1 L-proline and 0.8 mgL-1 AgNO3) were evaluated for their potential to induce callus in the three genotypes. All the media were supplemented with sucrose and five levels of 2, 4-Dichlorophenoxyacetic acid (2, 4-D) (0.5, 1.0, 1.5, 2.0 and 2.5 mgL-1). Resulting calli were matured on MS and N6 basal media supplemented with 60 g/L sucrose and similar concentration levels (0.5, 1.0, 1.5, 2.0 and 2.5 mgL-1) of 2, 4-D while the subsequent embryogenic calli were regenerated on hormone-free media. Transformability of these varieties was assessed via histochemical analysis of β-glucuronidase (GUS) reporter gene following Agrobacterium-mediated transformation. Statistical analyses were done using Statistical Analysis Software (SAS) and Graphpad Prism softwares with mean separations achieved at 95% confidence intervals. Of the 2 OPVs, KSTP’94 recorded the highest callus induction frequency (84.4%) while Namba Nane (45.6%) had the lowest. Similarly, KSTP, 94 had the highest mean of mature somatic embryos (59.7%) while Namba Nane recorded the lowest (16.4%). Assessment of regeneration frequencies from embryogenic calli revealed no significant differences among the 3 lines although CML 144 had the highest mean number of juvenile plantlets (36.7%). Analysis of transformation frequency (upon selection of calli on media with basta) showed that Namba Nane recorded the lowest transformation frequency (average 13.5%) some words missing. Transformation frequency (based on GUS positive calli) of these varieties ranged from 0.8 to 2.1%. This work therefore provides an empirical platform for potential introduction of useful genes into these varieties.